(untitled) (Medical Forum Monthly, 2024)
Aims and Objectives: The present study was therefore aimed to evaluate the role of relaxant prostaglandins in modulating the effect of Nebivolol on tracheal muscle of guinea pig since the exact mechanism underlying its effects on tracheal muscle has not been established yet. Background: The use of beta blockers is limited by their ability to produce bronchospasm in asthmatics. Third generation β blockers like Nebivolol may show better tolerability since there may be involvement of relaxant prostaglandins in its effect. However the involvement of prostaglandins in the respiratory effects of Nebivolol remains unexplored. The present study, carried out on isolated tracheal muscle strips of guinea pigs was designed to explore this controversy. Study Design: Experimental Study. Place and Duration of Study: This study was conducted at the Department of Pharmacology, Army Medical College, Rawalpindi since April 2010 to November 2010. Materials and Methods: Varying concentration of histamine ranging from 10-7M to 10-3M were used to plot a concentration response curve on the isolated tracheal muscle strips of guinea pig and was used as a control. The same concentration response curve was plotted in presence of a fixed concentration of Nebivolol 10-6M and then again in presence of a fixed concentration of Indomethacin 10-6M and Nebivolol 10-6M together in a series of experiments using six sets of isolated tracheal muscle strips in each case. Results: Nebivolol did not produce any significant shift in the concentration response curve in the presence and absence of Indomethacin. Conclusion: Nebivolol does not augment the histamine induced contraction of respiratory smooth muscle of guinea pig in the presence of Indomethacin, prostaglandin synthesis inhibitor indicating no role of relaxant prostaglandins in the sparing of respiratory smooth muscle by Nebivolol.